Spontaneous Hemorrhage into a Neurenteric Cyst of the Cerebellar Vermis - Khalatbari, M.R.; Moharamzad, Y. (Neuropediatrics, 2011)
Neurenteric cysts are rare benign developmental lesions of the central nervous system which are lined by endodermal cell-derived epithelium. Here we present a 17-year-old male who presented with acute onset headache and cerebellar ataxia. He was found to have a hyperdense lesion of the cerebellar vermis on CT scan. The lesion was hyperintense on T1-weighted and hypointense on T2-weighted MR images. Surgical resection of the cyst revealed hemorrhage into the neurenteric cyst.
Keywords: neurenteric cyst; cerebellar vermis; posterior fossa; hemorrhage